Candida albicans A Major Fungal Pathogen of Humans - Richardson, Jonathan (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book explores the biology of the fungal pathogen Candida albicans, its interaction with the human host, and current research that seeks to identify new ways to combat the health risks posed by C. albicans infection.